Expression of concern: Ameliorative effect of biofabricated ZnO nanoparticles of Trianthema portulacastrum Linn. on dermal wounds via removal of oxidative stress and inflammation. Issue 7 (3rd February 2023) - Yadav, Ekta; Singh, Deepika; Yadav, Pankajkumar; Verma, Amita
Abstract : Expression of concern for 'Ameliorative effect of biofabricated ZnO nanoparticles of Trianthema portulacastrum Linn. on dermal wounds via removal of oxidative stress and inflammation' by Ekta Yadav et al., RSC Adv., 2018, 8, 21621–21635, ; https://doi.org/10.1039/C8RA03500H .